2020
DOI: 10.20884/1.jm.2020.15.1.568
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polycrystalline Silicon from Rice Husk by Thermal Decomposition and Aluminothermic Reduction

Abstract: Polycrystalline silicon was extracted from rice husk by thermal decomposition and aluminothermic methods. Rice husk was thermally decomposed under various heat treatments and acid purifications. High purity silica of 99.81% was obtained by subsequent rice husk washing, pressure cooking in mixed chloride acid peroxide solution, and burning at 500oC for one hour. Aluminothermic reduction of silica was conducted at various calcination temperatures. It is found that 78.6% of silica was converted to silicon for cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In recent years, several studies have been conducted on recycling rice husks into Si-based materials using extracted SiO 2 powder. [4][5][6][7][8] In particular, several studies prepared SiC as a power semiconductor [9][10][11][12] and SiN as a high-hardness ceramics from rice husks. 9,10) Research has also been reported on the application of Si nanoparticles made from rice husks to the Li-ion battery anode.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have been conducted on recycling rice husks into Si-based materials using extracted SiO 2 powder. [4][5][6][7][8] In particular, several studies prepared SiC as a power semiconductor [9][10][11][12] and SiN as a high-hardness ceramics from rice husks. 9,10) Research has also been reported on the application of Si nanoparticles made from rice husks to the Li-ion battery anode.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, researchers have been considering the aluminothermic reduction method to produce Si from SiO 2 , mainly for use in the field of energy storage devices, e.g., as anode materials in secondary ion batteries. As a source of silicon, commercial quartz powder (SiO 2 ), waste glasses, and also rice husk have been reported (Radwan et al, 2005;Okutani, 2009;Lin et al, 2015;Zhou et al, 2016;Nuruddin et al, 2020). All of the reported works, so far, have focused on the powder metallurgical route to produce Si powder through this method.…”
Section: Introductionmentioning
confidence: 99%